Stereotactic Radiosurgery With and Without Checkpoint Inhibition for Patients with Metastatic Non-Small Cell Lung Cancer to the Brain: A Matched Cohort Study. (1st September 2019) - Shepard, Matthew; Xu, Zhiyuan; Donahue, Joseph; Muttikkal, Thomas Eluvathingal; Codeiro, Diogo; Hansen, Leslie; Mohammed, Nasser; Gentzler, Ryan D; Larner, James; Fadul, Camilo; Sheehan, Jason P
Abstract: INTRODUCTION: Immune checkpoint inhibitors (ICIs) improve survival in patients with advanced non-small cell lung cancer (NSCLC). Clinical trials examining the efficacy of ICI in patients with NSCLC excluded patients with untreated brain metastases (BM). As stereotactic radiosurgery (SRS) is commonly employed for NSCLC-BMs, we sought to define the safety, radiologic/clinical outcomes for patients with NSCLC-BM treated with concurrent ICI/SRS. METHODS: A retrospective, matched cohort study was performed on patients who underwent SRS to one or more NSCLC-derived BM. Two matched cohorts were identified: one who received ICI within 3-mo of SRS (concurrent-ICI) and one who did not (ICI-naive). Locoregional tumor control, peritumoral edema, and central nervous system adverse events were compared. RESULTS: A total of 17 patients (45-BMs) and 34 patients (92-BMs) comprised the concurrent-ICI and ICI-naive cohorts, respectively. Per RANO criteria, there was no difference in overall-survival (HR 0.99, 95% CI: 0.39-2.52) or CNS progression-free-survival (HR 2.18, 95% CI 0.72-6.62) between both groups. Similarly, the 12-mo local tumor control rate was 84.9% and 76.3% for tumors in the concurrent-ICI and ICI-naive cohorts, respectively ( P = .94). Nevertheless, patients receiving concurrent-ICI had increased rates of complete response for BMs treated with SRS (50% vs 15.6%; P = .012) per RANO criteria. There was a shorter median time to BM regression in the concurrent-ICI cohort (2.5-mo vs 3.1-mo, P < .001). There was no increased rate of radiation necrosis or intratumoral hemorrhage in patients receiving concurrent-ICI (concurrent-ICI: 5.9%; ICI-naive: 2.9%, P = .99). There was no difference in the rate of peritumoral edema progression across both groups (concurrent-ICI: 11.1%, ICI-naive: 21.7%; P = .162). CONCLUSION: The use of ICI/SRS to treat NSCLC-BM was well tolerated while providing more rapid BM regression. Concurrent-ICI did not increase rates of peritumoral edema, radiation necrosis, or intratumoral hemorrhage. Further studies are needed to evaluate whether concurrent ICI/SRS improves PFS/OS for patients with metastatic NSCLC.